2015
DOI: 10.3109/10826084.2015.1018538
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Severity Among Hispanic Emerging Adults in Higher Education: Understanding the Effect of Cultural Congruity

Abstract: Background Identifying and understanding determinants of alcohol use behavior among Hispanic college students is an increasingly important public health issue, particularly during emerging adulthood. Studies examining ethnocultural determinants of alcohol use behavior among Hispanic college students have focused on direct associations with cultural orientation (e.g., acculturation and enculturation); yet there is a need for research that accounts for the complex interplay of other culturally relevant sociocult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…However, Unger et al (18) reported about Latin American adolescent having a lower risk of tobacco and marijuana use but not alcohol, which they relate to the cultural and family norms related to alcohol. The recent study of Cano et al (19) supports the previous studies on Latin American gender norms related to alcohol use and cultural identity (7,20). For example, the term "machismo" is considered to contribute to adolescent behavior, including alcohol use (21,22).…”
Section: Introductionsupporting
confidence: 52%
“…However, Unger et al (18) reported about Latin American adolescent having a lower risk of tobacco and marijuana use but not alcohol, which they relate to the cultural and family norms related to alcohol. The recent study of Cano et al (19) supports the previous studies on Latin American gender norms related to alcohol use and cultural identity (7,20). For example, the term "machismo" is considered to contribute to adolescent behavior, including alcohol use (21,22).…”
Section: Introductionsupporting
confidence: 52%
“…A common factor shared by these theories is the role of negative reinforcement, whereby an individual is thought to use alcohol as a mechanism to alleviate depressive symptomatology or other undesired mood/emotional states (Baker et al, 2004). Empirical research findings lend support to these theoretical models because higher depressive symptomatology has been found to be associated with higher alcohol use among emerging adults (Gonzalez, Reynolds, & Skewes, 2011), including emerging adults of Hispanic heritage (Cano et al, 2015). …”
Section: Depressive Symptomatology Depressive Symptom Domains and Amentioning
confidence: 87%
“…Although cultural transactions can be positive (Cano, Vaughan, de Dios, Castro, Roncancio, & Ojeda, in press) or negative (Cano et al, 2015), we focused on negative cultural transactions. This follows from Acculturation Strain Theory , which proposes that enthnocultural orientation, operationalized as a unidimensional continuum of acculturation, is associated with increased experience of cultural stressors that in turn contribute to substance use and poor mental health outcomes (Vega, Zimmerman, Gil, Warheit, & Apospori, 1997).…”
Section: Cultural Transactionsmentioning
confidence: 99%